Analisis Metode Ohlson Dan Zmijewski Untuk Memprediksi Tingkat Kebangkrutan Pada Perusahaan Telekomunikasi Yang Terdaftar Pada Bursa Efek Indonesia - Ega Amalia Hidayah; Sunu Priyawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Corporate bankruptcy is a condition in which a company is unable to fulfill its obligations. Bankruptcy is considered predictable in companies that are still operating which will experience bankruptcy in the future. In order to determine the bankruptcy, it can be analyzed earlier using the Bankruptcy Analysis method. The purpose of this study was to determine the results of bankruptcy analysis at telecommunications companies using the Ohlson and Zmijewski analysis methods and to compare the results of the level of accuracy between the two methods with the type of qualitative research with a descriptive approach and purposive sampling method for the top ten telecommunications companies on the Indonesia Stock Exchange. The results show that the Ohlson method can find 14 out of 30 financial statements that are bankrupt, while the Zmijewski method can find 6 out of 30 financial statements of the companies studied. Other results from this study found that the Ohlson method has the highest level of accuracy in analyzing bankruptcy.